A shari’ah appraisal of the ijarah sukuk structure as implemented in Islamic capital markets - Adam Sa'ad, Auwal (2018)
Ijarah sukuk, as implemented in the global Islamic Capital Markets industry has been very attractive, and has been adopted by many of the largest developing economies. Ijarah sukuk is a modern facility innovated by Islamic Capital Market players to finance variuos projects and generate returns for investors. The paper highlights some important Shari'ah issues related to Ijarah sukuk issuances in Islamic Capital Markets.